The Hero™s Journey Stages and Character Archetypes in Anthony Horowitz™s Novel Alex Rider (Stormbreaker) - Zebua, Prades Adven Triman; Tangkas, I Wayan Dirgeyasa (Universitas Negeri Medan, 2023)
This research attempts to find out 1) the hero™s journey stages in Anthony Horowitz™s novel Alex Rider (Stormbreaker) 2) Character archetypes and their roles in helping or hindering the hero to complete the hero™s journey stages in Alex Rider (Strombreaker). The research is conducted using qualitative research methods, the technique of data analysis is descriptive qualitative method, the instrument for collecting the data is documentary sheet. The source of data used for this research is Alex Rider (Stormbreaker) novel. The results of this study showed that the seventeen (17) stages formulated by Joseph Campbell are found in the novel. Furthermore, this study also showed that the seven (7) different archetypes formulated by Christopher Vogler are found in the novel. This concludes that the hero™s journey stages and the character archetypes formulas that the first data collected by Joseph Campbell was from oral tradition stories is found to be applicable to modern novels.